PROSES PEMBERIAN PINJAMAN KREDIT MODAL KERJA DARI PT. BANK RAKYAT INDONESIA CABANG SAMARINDA UNIT ABDUL WAHAB SYAHRANI - Ade Sulistya Ningrum (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT Lending is one of the bank's business activities related to channeling bank funds to the public that can be used by business actors to develop and enlarge their businesses both directly and indirectly can help the distribution of public income. In the implementation of the process of lending and borrowing working capital loans provided by banks, there have been many problems that arise, namely data and requirements that are incomplete or the data provided is not in accordance with the requirements. Then in the implementation of credit problems can occur such as problem loans or bad credit.This study uses a type of normative legal research that is a legal research method carried out by examining mere literature or secondary data using the Law and Concept approach.The results of the study stated that the Process of Providing Credit in Providing Working Capital Loans from PT. Bank Rakyat Indonesia Samarinda Branch Unit AW. Syahrani according to Law Number 10 of 1998 has the following steps: Fill out the Loan Submission Form, Complete the loan conditions, BI Cheking (checking good or bad customer history), Interview, Survey of feasible / unsuitable business places, Credit analysis , Preparation of credit agreements, Signs of debt recognition letters and other agreements and Realization of credit (disbursement of funds) while Efforts Made by PT. Bank Rakyat Indonesia Samarinda Branch Unit AW. Syahrani in Overcoming Non-Performing Loans is by way of Restructuring Credit, Billing With the Assistance of Third Parties, Direct Billing By Bank Officers and Special Policy To the Debtor Keywords: Provision of Credit, Working Capital